Motivations, constraints, and negotiation strategies of state university students in pursuing their creative hobbies - Valladarez, Jessa Mae
This study investigates the motivations, constraints, and negotiation strategies employed by students at the University of the Philippines (UP) in pursuing creative hobbies. Through a comprehensive survey and in-depth interviews, the research identifies the predominant intrinsic and extrinsic motivations driving students, such as intellectual stimulation and potential financial gains. The study reveals that while structural constraints like financial limitations and time pressures significantly impact participation, intrapersonal constraints, including self-doubt and emotional challenges, also play a crucial role. Despite these barriers, students employ various negotiation strategies, including skill acquisition, resource improvisation, and time management, to sustain their creative activities. The findings highlight the importance of motivation and negotiation strategies in overcoming constraints and sustaining participation in creative hobbies, with motivation correlating with higher negotiation strategies which then mitigates the constraints of students. The research contributes to understanding how UP students balance their academic and personal responsibilities and internal struggles, with creative pursuits, highlighting the dynamics between motivation, constraints, and negotiation strategies in fostering a fulfilling engagement in creative hobbies.